Gwendy's final task [compact disc, unabridged] - King, Stephen, 1947-; Chizmar, Richard, 1965- (Simon & Schuster Audio, 2022)
When Gwendy Peterson was twelve, a mysterious stranger named Richard Farris gave her a mysterious box for safekeeping. It offered treats and vintage coins, but it was dangerous. Pushing any of its seven colored buttons promised death and destruction. Years later, the button box entered Gwendy's life again. A successful novelist and a rising political star, she was once again forced to deal with the temptation that box represented. Now, evil forces seek to possess the button box and it is up to Senator Gwendy Peterson to keep it from them. At all costs. But where can you hide something from such powerful entities?